PENGARUH KUALITAS PRODUK, CITRA MEREK DAN HARGA TERHADAP MINAT PEMBELIAN SMARTPHONE MEREK SAMSUNG - Henry Casandra Gultom; Renorian Ranandaru; Ratih Hesty Utami Puspitasari (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2021)
This study aims to determine the effect of product quality, brand image and price on interest in purchasing Samsung smartphones at FEB PGRI University Semarang. The population in this study were all students of FEB PGRI University Semarang, the sample in this study was 100 respondents. In conducting research data collection using a Likert scale with 5 assessment criteria and to measure 17 statement items. The sampling technique in this research uses a type of probability sampling. The data analysis technique is multiple linear regression analysis. The result of this analysis states that product quality partially influences purchase intention, brand image does not partially influence purchase interest...